A Bibliometric And Sentiment Analysis On Sharia Credit Card - Mu’adzah, Nadiyah; Rachmad, Dedy (LPPM ISNJ Bengkalis, 2024)
This research aims to analyze previous research trends regarding Sharia credit cards and the sentiment of this research regarding law from an Islamic perspective. This research is a literature review that uses secondary data from 55 articles related to Sharia credit cards on Dimensions.ai. The data analysis techniques used are meta-analysis, bibliometric, and sentiment analysis, which are processed using Microsoft Excel 2019, VOSViewer, and SentiStrength software. The results of this study indicate that the development of scientific literature publications on Sharia credit cards fluctuated yearly. Sentiment analysis shows a tendency for positive perceptions rather than negative perceptions about the existence and laws of Sharia credit cards, but neutral perceptions dominate. This study found five relevant research topics related to Sharia credit cards. This study can be used as a reference in identifying influential authors, articles, and journals as well as relevant topics so that future researchers will find it easier to find references and topics of interest to developing literature on Sharia credit cards.